A three‐dimensional chiral crystal structure constructed from a chiral triazolate ligand showing an SrSi2 topology: poly[bis(μ3‐3, 5‐diethyl‐1, 2, 4‐triazolato‐κ3N1:N2:N4)trisilver nitrate]. (12th November 2013) - Jiang, Feng; Dai, Lin; Shi, Yiqiang; Wang, Zhixiang
<x xml:space="preserve">Abstract</x> In the title metal–organic framework (MOF), [Ag3(C6H10N3)2]NO3n, the AgI cation is coordinated by two N atoms from two different 3, 5‐diethyl‐1, 2, 4‐triazolate (detz) ligands in a linear configuration. Each AgI cation is then connected to two adjacent AgI cations via a μ3‐N1:N2:N4‐detrz ligand, resulting in a three‐dimensional chiral silver–triazolate structure showing an SrSi2 (srs) net with 103 topology.